163k views
4 votes
Write a rule in coordinate form for the translation from Triangle EFG to Triangle

E'F'G'.
(x,y)-->(x+2, y-1)
(x,y)-->(x+1, y-2)
(x,y)-->( X-2, y + 1)
(x,y)-->(x+3, y +2)

Write a rule in coordinate form for the translation from Triangle EFG to Triangle-example-1
User Romor
by
4.3k points

1 Answer

1 vote

Answer:

1st option

Explanation:

Consider the coordinates of F and F'

F (- 3, 4 ) and F' (- 1, 3 )

To go from - 3 → - 1 in the x- directions , means adding 2

To go from 4 → 3 in the y- direction means subtracting 1

Then translation rule is

(x, y ) → (x + 2, y - 1 )

User Steve Harman
by
4.6k points